The structural determinants of insulin-like peptide 3 activity - Bathgate, Ross A.; Zhang, Soude; Hughes, Richard A.; Rosengren, Johan; Wade, John D. (Frontiers in Endocrinology, 2012)
INSL3 is a hormone and/or paracrine factor which is a member of the relaxin peptide family. It has key roles as a fertility regulator in both males and females. The receptor for INSL3 is the leucine rich repeat (LRR) containing G-protein coupled receptor 8 (LGR8) which is now known as relaxin family peptide receptor 2 (RXFP2). Receptor activation by INSL3 involves binding to the LRRs in the large ectodomain of RXFP2 by residues within the B-chain of INSL3 as well as an interaction with the transmembrane exoloops of the receptor. Although the binding to the LRRs is well characterized the features of the peptide and receptor involved in the exoloop interaction are currently unknown. This study was designed to determine the key INSL3 determinants for RXFP2 activation. A chimeric peptide approach was first utilized to demonstrate that the A-chain is critical for receptor activation. Replacement of the INSL3 A-chain with that from the related peptides INSL5 and INSL6 resulted in complete loss of activity despite only minor changes in binding affinity. Subsequent replacement of specific A-chain residues with those from the INSL5 peptide highlighted that the N-terminus of the A-chain of INSL3 is critical for its activity. Remarkably, replacement of the entire N-terminus with four or five alanine residues resulted in peptides with near native activity suggesting that specific residues are not necessary for activity. Additionally removal of two amino acids at the C-terminus of the A-chain and mutation of Lys-8 in the B-chain also resulted in minor decreases in peptide activity. Therefore we have demonstrated that the activity of the INSL3 peptide is driven predominantly by residues 5-9 in the A-chain, with minor additional contributions from the two C-terminal A-chain residues and Lys-8 in the B-chain. Using this new knowledge, we were able to produce a truncated INSL3 peptide structure which retained native activity, despite having 14 fewer residues than the parent peptide.